2005
DOI: 10.1007/s11103-005-1728-y
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of changes in wheat gene expression after treatment with three antifungal compounds

Abstract: The two fungicides azoxystrobin and fenpropimorph are used against powdery mildew and rust diseases in wheat (Triticum aestivumL). Azoxystrobin, a strobilurin, inhibits fungal mitochondrial respiration and fenpropimorph, a morpholin, represses biosynthesis of ergosterol, the major sterol of fungal membranes. Although the fungitoxic activity of these compounds is well understood, their effects on plant metabolism remain unclear. In contrast to the fungicides which directly affect pathogen metabolism, benzo(1,2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 72 publications
(79 reference statements)
1
47
0
1
Order By: Relevance
“…Other authors studied the effects of fungicides containing such active substances as strobilurins (Ray et al 2004, Ruske et al 2004, Pasquer et al 2005, epoxiconazole (Benton andCobb 1995, Ray et al 2004) and cyprodinil (Ray et al 2004), and found that all of them positively affected crop yields when applied at recommended doses. This meets the expectations of both producers and farmers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors studied the effects of fungicides containing such active substances as strobilurins (Ray et al 2004, Ruske et al 2004, Pasquer et al 2005, epoxiconazole (Benton andCobb 1995, Ray et al 2004) and cyprodinil (Ray et al 2004), and found that all of them positively affected crop yields when applied at recommended doses. This meets the expectations of both producers and farmers.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides enable to achieve higher crop yields (Ray et al 2004, Pasquer et al 2005, Valenciano et al 2006), but at the same time negatively affect natural environment, including the soil environment, disturbing its homeostasis.…”
mentioning
confidence: 99%
“…BTH is a functional analog of SA and one of the so-called plant activators, which all induce the same characteristic set of systemic acquired resistance (SAR) genes; this function of BTH has also been observed in wheat (Görlach et al 1996, Pasquer et al 2005. Prior research has indicated that BTH induces acquired resistance in wheat, including resistance to powdery mildew (Erysiphe graminís), leaf rust (Puccinia recondite), and leaf spot (Septoria spp.)…”
Section: Discussionmentioning
confidence: 97%
“…Systemic resistance has already been successfully induced in other plants against viruses, and because no transgenic techniques are employed it should be more commercially acceptable. However, it should be borne in mind that some concern has been expressed about the applicability of induced resistance in the field compared to the laboratory or glasshouse, as plants may already be at or near their limit from pre-existing stresses [67,68]. Another consideration is that the applicability of this technique is likely to be cultivar dependent, as has been found in tomatoes [69].…”
Section: Discussionmentioning
confidence: 99%